Cultivation of leucena intercropped with bean, maize and cotton - Filho, Orlando Monteiro de Carvalho (Pesquisa Agropecuaria Brasileira, 1992)
Ibis work was developed on an Eutrophic Cambisol, in Poço Verde, SE, Brazil, from 1984 to 1987. It aimed to make compatible the exploitation of leucaena (Leucaena leucocephala Lam. de Wit) intercropped with maize, bean and cotton, without causing, however, signiflcative changes in the production systems being used by small holders. Seedlings were planted with a spacing of 2.5 m between rows and 1.0 m between plants, both in the sole crop and intercrop. In the intercropping systems crops were planted between the rows of leucaena. Plants were pruned (leaves + branches with a diameter lesser than 0.5 m) as they came to flowering and every year, at the beginning of rainy season, leucaena plants were cut 0.20 m above soil and the crops were planted. In the second year, there was no difference in the behavior of leucaena in sole crop and intercrop. Leucaena yielded about 9,000 kg of dry matter/ha/year, corresponding to about 2,500 kg of crude protein. Bean and maize yields were expressive. Nevertheless, the use of cotton revealed to be inadvisable.